A DESCRIPTIVE STUDY OF RICE VALUE CHAIN ACTORS IN INDONESIA (Case Study Purwakarta, Karawang, Cikampek, and Subang) - Maria Widyarini (Research Report - Humanities and Social Science, 2012)
The role of rice price policy in Indonesia to stimulate rice productivity growth is facing some difficulties. These will give significant affect on the stability rice value chains. The increasing of rice price in the market is suspected by external factors such as weather, the decreased of rice supplies and so on. Practically, the increasing rice price is lower than the cost of rice planting. The issues which be discussed in this study concerns the factors influencing rice price fluctuation in domestik market. The price dynamics all related actors were analysed  based on actors behavior on rice value chain using context mechanism output. This study contributes to the better understanding of price fluctuations more sensible that is the interelation between conceptual theory with existing market conditions. The descriptive study is employed to figure out the rice price fluctuations within the rice value chains as described in Figure 3.1. indicates two components, namely decision making and social interactions among actors. In this stage, observations and interviews are conducted in order to get better understanding and to investigate with emphasizing on factors affecting price fluctuations and social interactions on rice value chains (behavioral of rice price transformation along value chain).The rice marketing system along value chain has been done imperfectly due to (1) climate change ; (2) lack of capital (at farmers positition) ;(3) information assymetry of rice price value chain (less transparency of market prices and costs provides an adequate market signals to middleman to take part on rice price; decision of selling and buying handled by middleman; price reflects cost of seller ) ;(4) rice import and (4) inability of government to give sanctions to someone who violate (such as illegal rice import found in market, rice price fluctuations).  But, the long working relationship/social relationship found among actors related such as trust, norm and role. These is Increasing scale of marketing efficiency of rice production facilities and processing works by having colaboration among actors such as rice field owner, saprodi shop, peasant labour, miller and middleman (trasher, retailer and wholesaler). Moreover, the growth of private label in rice retail and strong customer segmentation  in retail market between rice premium and mid-range impose the rice competition among middleman (traders).Further, work on value chain analysis allows structuration theory to be more critically examined in this context and the potential connections with other theoretical frameworks to be explored for the next research plan.